Mood instability, depression, and anxiety in pregnancy and adverse neonatal outcomes - Hua Li; Angela Bowen; Rudy Bowen; Nazeem Muhajarine; Lloyd Balbuena (BMC, 2021)
Abstract Background Antenatal women experience an increased level of mood and anxiety symptoms, which have negative effects on mothers' mental and physical health as well as the health of their newborns. The relation of maternal depression and anxiety in pregnancy with neonate outcomes is well-studied with inconsistent findings. However, the association between antenatal mood instability (MI) and neonatal outcomes has not been investigated even though antenatal women experience an elevated level of MI. We sought to address this gap and to contribute to the literature about pregnancy neonate outcomes by examining the relationship among antenatal MI, depression, and anxiety and neonatal outcomes. Methods A prospective cohort of women (n = 555) participated in this study at early pregnancy (T1, 17.4 ± 4.9 weeks) and late pregnancy (T2, 30.6 ± 2.7 weeks). The Edinburgh Postnatal Depression Scale (EPDS) was used to assess antenatal depressive symptoms, anxiety was measured by the EPDS anxiety subscale, and mood instability was measured by a visual analogue scale with five questions. These mood states together with stress, social support, as well as lifestyle were also examined in relation to neonatal outcomes using chi-square tests and logistic regression models. Results Mood instability, depression, and anxiety were unrelated to adverse neonatal outcomes. Only primiparous status was associated with small for gestational age after Bonferroni correction. Conclusions We report no associations between antenatal mood symptoms including MI, depression, and anxiety and neonatal outcomes. More studies are required to further explore the relationship between antenatal mood instability, depression, and anxiety and neonatal outcomes.